The Effect of Placement, Work Environment, and Job Satisfaction on The Performance of District Court Employees in South Sumatera - Utami, Yurima; Rahayu, Sri; Choiriyah, choriyah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study aims to determine whether placement, work environment, and job satisfaction affect the performance of District Court employees in South Sumatra. The type of research is associative-causality quantitative. The sample in this study were civil servants at the Palembang District Court, Pangkalan Balai, Kayuagung, Sekayu, and Baturaja, with a total of 114 people. The study uses primary data and secondary data. The results of simultaneous hypothesis testing show that simultaneous placement, work environment, and job satisfaction significantly influence the performance of South Sumatra District Court employees. The results of testing the hypothesis partially show that placement does not significantly influence the performance of District Courts South Sumatra employees. The results of testing the hypothesis show that the work environment significantly influences the performance of employees of the District Courts in South Sumatra. The results of testing the hypothesis show that job satisfaction significantly influences the performance of employees of the District Courts in South Sumatra